DO MACROECONOMIC VARIABLES INFLUENCE INFLATION ANALYSIS FROM MALAYSIA WITH A QUANTITATIVE APPROACH - NorHasniza Mohamad Noh; Shahariah Asmuni; Masturah Ma'in; Saliza Sulaiman; Zuraidah Ismail (Jurnal Visionida, 2026)
ABSTRACT This paper investigates the influence of some key macroeconomic variables on the inflation rate in Malaysia using annual time-series data for the period of 1982-2022. The relationships between inflation and four major indicators-unemployment rate, economic growth, net imports, and interest rate-are investigated in this paper using the multiple linear regression technique based on the OLS method. The findings indicate that inflation in Malaysia has been significantly affected by fluctuations in those macroeconomic factors. From the estimates, economic growth, unemployment rate, and interest rate show a significant effect on inflation, implying that high output, employment, and cost of borrowing are associated with escalating price levels. On the other hand, net imports show no significant effect on inflation. Generally, the results provide useful insights into the dynamics of Malaysia's inflationary behavior and emphasize that coordinated macroeconomic policies are crucially important to achieve price stability along with economic growth